In-Hospital Outcomes Comparison Between Off-Pump and On-Pump CABG: Indonesian Tertiary Center Experience - Dewi, Triwedya Indra; Jungjunan, Ridho; Raharjo, Pradana Pratomo; Rezkita, Aliya Rahmadewi; Hidayat, Syarief; Martha, Januar Wibawa; Nusjirwan, Rama; Akbar, Mohammad Rizki (International Journal of Integrated Health Sciences, 2025)
Background: Coronary artery disease (CAD) often requires revascularization. Coronary artery bypass grafting (CABG) is a cornerstone intervention that improves patients’ survival. Both on-pump and off-pump CABG have their own advantages and limitations, with reported outcomes vary across studies.Objective: to investigate the differences in the outcomes of patients undergoing off-pump and on-pump CABG.Methods: A retrospective cohort study was performed on 186 patients aged ≥18 years undergoing on-pump or off-pump CABG between June 2020 and December 2023. Outcomes included were all-cause mortality, postoperative acute renal failure, length of postoperative stay, and complete revascularization rate. Comparative analysis was conducted using Chi-Square test and independent T-test. Multivariate analysis, including logistic regression tests, was carried out to identify independent predictors associated with each outcome.Results: The on-pump group presented more diabetes (42.9% vs. 28.4%; P=0.040) and lower left ventricular ejection fraction (LVEF) values (43 [IQR 16–79] vs. 53 [23–75]; P=0.001). Patients in this group also had higher rates of postoperative renal failure (61.5% vs. 24.2%; P<0.001), longer stays (64.8% vs. 41.1%; P=0.001), and better complete revascularization (98.9% vs. 92.6%; P=0.035), but no significant difference in mortality (16.5% vs. 13.7%; P =0.594). Multivariate analysis identified diabetes, LVEF ≤40%, and postoperative renal failure as predictors of mortality.Conclusions: On-pump CABG is associated with higher rates of complete revascularization. However, the adoption of this technique is linked to a higher risk of postoperative acute kidney failure and prolonged hospital stays. No difference in mortality is observed between those with off-pump and on-pump.